Post Earthquake Aggradation Processes to Hide Surface Ruptures in Thrust Systems: The M8.3, 1934, Bihar‐Nepal Earthquake Ruptures at Charnath Khola (Eastern Nepal). Issue 8 (14th August 2019) - Rizza, M.; Bollinger, L.; Sapkota, S. N.; Tapponnier, P.; Klinger, Y.; Karakaş, Ç.; Kali, E.; Etchebes, M.; Tiwari, D. R.; Siwakoti, I.; Bitri, A.; Bes de Berc, S.
Abstract: The Charnath Khola is a large river crossing the Himalayan thrust system in the region devastated by the great M8.3 1934 Bihar‐Nepal earthquake. Fluvial terraces are abandoned along the river and at the base of a 20‐m high cumulative thrust escarpment. A trench across the fault scarp exposed Siwalik mudstone/siltstone overthrusting Quaternary units and three colluvial wedges interfingered with fluvial sands. The 85 accelerator mass spectrometry radiocarbon dates, from detrital charcoals sampled in the trench, a river cut and river terraces, constrain the timing of the sedimentary processes following the last two major earthquakes, in 1934 and 1255 CE. Although several samples straddle the main earthquake horizon, associating it with the 1934 earthquake, based solely on radiocarbon ages, remains challenging. The 49 detrital charcoal ages found in the pre‐earthquake and postearthquake units fall between 65 and 225 BP, a period with a flat calibration curve. Many of these radiocarbon ages are suspected to include a part due to inbuilt time (i.e., age of the wood at the time of burning), transport time, and reworking processes, which are difficult to resolve. Considering these ages at their face value could lead to dates older than the actual earthquake dates. We suggest that a part of this chronological bias is also related to a local postseismic aggradation pulse of 4 to 5 m of sediments, which is documented in the trench and terraces. This fluvial sequence, hiding the most recent surface rupture, is likely related to landslide‐sediment deposition triggered by the 1934 Bihar‐Nepal earthquake. Key Points: Evidence for 1934 and 1255 AD surface ruptures at Charnath Khola, eastern Nepal Aggradation pulses at the Charnath Khola follow large surface rupturing earthquakes Overlooking the predeposit processes of detrital charcoal samples could lead to paleo‐earthquake dates older than the actual earthquake dates